Multiple blockholders, power, and firm value - Basu, Nilanjan; Paeglis, Imants; Rahnamaei, Mohammad (Journal of Banking & Finance, 2016)
Using a comprehensive sample of US firms we show that most of them have multiple blockholders whose presence and ownership stakes lead to a significant difference between ownership and power. This difference matters. First, we find that insider power (ownership) is negatively (positively) related to firm value. Second, we show that outsider power is positively related to firm value. Our direct blockholder-level measure of power explains firm value over and above the explanatory power of firm-level measures used in the literature (such as the number of blockholders and the dispersion of their ownership stakes).